The effects of romantic love on mentalizing abilities - Wlodarski, R; Dunbar, RIM (American Psychological Association, 2014)
The effects of the human pair-bonded state of “romantic love” on cognitive function remain relatively unexplored. Theories on cognitive priming suggest that a state of love may activate love-relevant schemas, such as mentalizing about the beliefs of another individual, and may thus improve mentalizing abilities. On the other hand, recent functional MRI (fMRI) research on individuals who are in love suggests that several brain regions associated with mentalizing may be “deactivated” during the presentation of a love prime, potentially affecting mentalizing cognitions and behaviors. The current study aimed to investigate experimentally the effect of a love prime on a constituent aspect of mentalizing—the attribution of emotional states to others. Ninety-one participants who stated they were “deeply in love” with their romantic partner completed a cognitive task involving the assessment of emotional content of facial stimuli (the Reading the Mind in the Eyes task) immediately after the presentation of either a love prime or a neutral prime. Individuals were significantly better at interpreting the emotional states of others after a love prime than after a neutral prime, particularly males assessing negative emotional stimuli. These results suggest that presentation of a love stimulus can prime love-relevant networks and enhance subsequent performance on conceptually related mentalizing tasks.